2023
DOI: 10.1149/1945-7111/acc09c
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Deposition with Redox Replacement of Lanthanum with Uranium in Molten LiCl-KCl

Abstract: Electrochemical recovery of dilute concentrations of actinides from spent nuclear fuel would reduce the longevity of storing high-level nuclear waste. Electrochemical deposition with redox replacement (EDRR) is used in a molten salt medium for the selective electrochemical recovery of uranium in the presence of excess concentrations of lanthanum. In each EDRR cycle, after a short electrodeposition pulse, the deposited lanthanum is spontaneously replaced by uranium at open circuit. After repeated cycles, uraniu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The study conducted by Eakin, which revealed that, within a limited electrolysis time, uranium would selectively deposit at the active site on the surface of the tungsten electrode and react with a portion of LiCl-KCl to form a monolayer of uranium. 47 Pseic studied the morphological changes of uranium metal on the electrode surface during potential scanning of CV, the SEM images of the surface of the tungsten electrode are shown in Fig. 5.…”
Section: = ( )mentioning
confidence: 99%
“…The study conducted by Eakin, which revealed that, within a limited electrolysis time, uranium would selectively deposit at the active site on the surface of the tungsten electrode and react with a portion of LiCl-KCl to form a monolayer of uranium. 47 Pseic studied the morphological changes of uranium metal on the electrode surface during potential scanning of CV, the SEM images of the surface of the tungsten electrode are shown in Fig. 5.…”
Section: = ( )mentioning
confidence: 99%
“…14 The higher solubility of lanthanides relative to that of actinides in chloride molten salts can be used to process spent nuclear fuel, as demonstrated in the chloride salt electrorefining process at Idaho National Laboratory. 15 Previously, solubilities of LaF 3 , CeF 3 , and SmF 3 in LiF− BeF 2 −UF 4 (62.8−36.4−0.8 mol %) salt as well as YF 3 and CeF 3 in NaF−BeF 2 (61−39 mol %) salt were measured to support MSRE. 16 Solubilities are also published for ARE salts, including the measurements of BaF 2 , LaF 3 , CeF 3 , SmF 3 , and YF 3 in NaF−ZrF 4 −UF 4 (50−46−4 mol %) salt.…”
Section: Introductionmentioning
confidence: 95%
“…These fission products affect neutronics and system operation through parasitic absorption of neutrons . The higher solubility of lanthanides relative to that of actinides in chloride molten salts can be used to process spent nuclear fuel, as demonstrated in the chloride salt electrorefining process at Idaho National Laboratory …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advancements in uranium electrodeposition, utilizing molten salts and covalent organic frameworks, have been demonstrated with various substrates, including Polyaniline/Graphite sheet, phytic acid-doped polypyrrole/carbon felt electrode, and tungsten electrodes [20]. Recently, investigations into the cathodic reduction of U(III) ions on inert (tungsten) and reactive (gallium, cadmium) electrodes were conducted at temperatures ranging from 623 K to 923 K using cyclic and square wave voltammetry [21].…”
Section: Introductionmentioning
confidence: 99%